Rapid disappearance of gouty tophi of the foot by resection of massive gouty tophi of the opposite foot in a patient with hyperuricaemia: a case report. (2nd January 2020) - Takakubo, Yuya; Imamura, Yuta; Tezuka, Hiroshi; Okada, Soichiro; Naganuma, Yasushi; Ito, Juji; Sugawara, Masato; Yang, Suran; Oki, Hiroharu; Sasaki, Akiko; Sasaki, Kan; Konta, Tsuneo; et al.
Abstract: Gouty tophi occur less frequently and disappear only with modern medication therapy for symptomatic or asymptomatic hyperuricaemia. However, the medication may require a long time to take effect due to the systemic urate pool associated with massive gouty tophi. We present the case of a 37-year-old woman who suffered from massive gouty tophi of both feet due to hyperuricaemia. After resection of the massive gouty tophi from her right foot and treatment with uricemia medication, the gouty tophi of her opposite foot disappeared rapidly due to reducing the patient's systemic urate pool with intensification of drug medication.